THE ABILITY OF FINANCIAL RATIOS, INFLATION AND GROSS DOMESTIC PRODUCT (GDP) TO PREDICT THE GROWTH OF COMPANY PROFIT - Ika Wahyu Nurrini; Sukirno Sukirno (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
This research was conducted to gather information about the influence of Current Ratio, Total Asset Turnover, Leverage Ratio, Profit Margin, Return on Asset, Inflation and Gross Domestic Product on profit growth at service companies in Indonesia Stock Exchange partially and simultaneously. The purposive sampling technique was used to collect the samples. The amount of samples in this research were the 40 service companies in the property and real estate sector listed in the Indonesia Stock Exchange in the 2014-2016 period. The classic assumption test was done before the multiple linear analysis, t test, F test and R2 were used to implement the hypothesis test. The test results showonly partially, the Return On Asset has a positive and significant effect to profit growth, while the variable of Current Ratio, Total Asset Turnover, Leverage Ratio, Profit Margin, Inflation and Gross Domestic Product have insignificant effects to profit growth. Simultaneously, the Current Ratio variable, Total Asset Turnover, Leverage Ratio, Profit Margin, Return On Asset, Inflation and Gross Domestic Product have significant effects to profit growth.Keywords:Current Ratio, Gross Domestic Product, Inflation, Leverage Ratio, Profit Growth, Profit Margin, Return On Asset, and Total Asset Turnover